The Listening Guide:: A Socio-Cultural Analysis of Arab Women Leaders' Stories - Shapira, Tamar; Arar, Khalid (Narrative Works)

(untitled) (The University of New Brunswick, 2017)
This article describes application of a psychological-narrative inquiry method to socio-cultural research. The Listening Guide method is used to identify patterns in life stories of Arab women leaders in Israel. The first study examines the stories of ten women leaders in Arab public schools. The second and third studies are part of research investigating female Arab managers working in educational and welfare systems in Israel. The Listening Guide method reveals the construction of the narrators’ personal, social and professional lives and how life stories are translated into reality-altering action in the narrators’ society.